Concurrence of multiple sclerosis and glioma. Issue 5 (May 1974) - Currie, S.; Urich, H.
Abstract : Three cases are reported of concurrence of malignant gliomas (astrocytomas and glioblastomas) with multiple sclerosis (MS). This situation may lead to considerable diagnostic difficulties, yet an accurate appraisal is of prognostic, if not therapeutic, value. There is suggestive but inconclusive evidence that the two conditions may be causally related, malignant astrocytic tumours arising from plaques of MS. The small number of reported cases makes statistical analysis impossible, but the scanty literature may not reflect the true incidence.